Studi Kepustakaan Tersistem Desain Ruang Gender pada Masjid Berdasarkan Mazhab Utama dalam Islam - Azzah Juharida; Noor Cholis Idham; Nensi Golda Yuli (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
This research analyzes and explores theories from various references regarding the design of gender spaces in mosques based on Islam's primary schools of thought. The literature review method in this research uses the Publish or Perish and Google Scholar with the keyword "gender in mosque". From the results of reference screening, 16 journals were found with topic classification based on timeline, school of thought and architectural objects. The results based on the timeline have stable graphs each year, while the religious stream and architectural objects are less stable because of their unavailability. Based on gender space architectural objects was found in 6 papers and only in the Syafi'i and Hanafi schools. Meanwhile, no references were found in the Maliki and Hambali schools. The Syafi'i School of Religion pays more attention to women in worship matters. However, not all apply the same principles because local community customs and customs hamper their application. Meanwhile, in the Hanafi School, gender space arrangements are more varied due to the influence of local culture, politics, and religious modernism.